The rigid flexibility model for strategic outcomes: lessons learned from the treaty of Hudaybiyyah - Fazli Idris,; Ahamad Asmadi Sakat, (Penerbit Universiti Kebangsaan Malaysia, 2015)
This article discusses simplicity and discipline, the two elements of rigid flexibility model to explain strategic outcomes using an important historical event. The objective is to strengthen the validity of the model and provide constructive arguments for the model to be applied in a new setting. In theory refinement, the richness and in-depth descriptions of constructs under consideration are highly sought. A historical event called the Treaty of Hudaybiyyah is portrayed; with decisions and actions that came out of the treaty are explained using the rigid flexibility framework. Analyzing this historical case, we proposed that there are related concepts, important practices and procedures that match the concepts of simplicity and discipline comparatively. It shows that the strategic outcomes could be realized using concepts and practices such as tolerance, consultations, giving preference for strategic outcomes, discipline in following order, simplified and easy-to-understand communication approach and emphasis on standard performances.